2022
DOI: 10.15507/1991-9468.107.026.202202.312-330
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Publications in Russia: A Literature Review on How to Influence University Researchers

Abstract: Introduction. Under the growing role of university science in Russia, special attention is paid to improving the quality of scientific publications of Russian university researchers in leading international and Russian journals. To understand the direction of scientific discourse on this issue, the authors explored scientific publications that address the tools to influence Russian university researchers to publish in journals indexed by Scopus or Web of Science. Materials and Methods. Articles found up to 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Logically, Scientometrics and Research Evaluation were identified as primary publishing sources (Figure 3), as the topic of RE fits closely within the scope of these journals. The great interest of Russian authors in RE in recent years (Figure 4) stems from the intro of a country-specific research evaluation system for prioritizing science [33], [38], [48], [54]. The increased interest of authors from the UK, New Zealand and the USA (Figure 4) can be explained by the constant improvements in their RE systems introduced there long ago [17], [44], [47].…”
Section: Discussionmentioning
confidence: 99%
“…Logically, Scientometrics and Research Evaluation were identified as primary publishing sources (Figure 3), as the topic of RE fits closely within the scope of these journals. The great interest of Russian authors in RE in recent years (Figure 4) stems from the intro of a country-specific research evaluation system for prioritizing science [33], [38], [48], [54]. The increased interest of authors from the UK, New Zealand and the USA (Figure 4) can be explained by the constant improvements in their RE systems introduced there long ago [17], [44], [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other papers [12], [22], [23] also indicate factors driving management to influence researchers to increase WoS/Scopus publications, but mentioning them in a different context and without explicitly defining them as "motivational factors". University ranks, grants, prestige and "publish-orperish" pressure are most commonly mentioned.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Among the latter, the university management is of great importance. It is defined as a key internal stakeholder in the scientific literature [11], thanks to the rich set of tools at its disposal to influence researchers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Водещите университети демонстрират високи постижения предимно в изследователската дейност (Meek & Davies, 2009). Преподавателите на тези университети се считат за по-ефективни (Lambovska & Raitskaya, 2022). Повишаването на ефективността на научноизследователската дейност води до увеличаване на имиджа на университета, което означава по-добри възможности за привличане и задържане на висококвалифициран академичен персонал, подобряване на разпознаваемостта на университета и увеличаване на кандидатстудентите.…”
Section: основни критерии за оценяване на научноизследователската дей...unclassified